2006
DOI: 10.1080/02701367.2006.10599346
|View full text |Cite
|
Sign up to set email alerts
|

Lectures and Symposia Peer-Reviewed Abstracts

Abstract: The purpose of this study was to examine changes in landing performance during fatigue that could result in increased stress fracture injury risk. Five participants performed nonfatigued and fatigued drop landings (0.60 m), while ground reaction force (GRF), electromyographic (EMG) activity, and kinematics were recorded. Fatigue was defined as a 5-20% reduction in vertical jumping performance. Single-subject analyses revealed that all participants were affected (p < or = .05) by fatigue. Post hoc comparisons r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…To be consistent with the landing mode under a prefatigue condition, appropriate control of the landing posture is required as a protective behavior in terms of maintaining the impact force and LR [30]. However, James et al also found a greater peak GRF/LR during a DL task using the fatigue protocol of stretch shortening cycle exercise [18]. Therefore, whether the characteristics of the GRF/LR would change with the development of fatigue still needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To be consistent with the landing mode under a prefatigue condition, appropriate control of the landing posture is required as a protective behavior in terms of maintaining the impact force and LR [30]. However, James et al also found a greater peak GRF/LR during a DL task using the fatigue protocol of stretch shortening cycle exercise [18]. Therefore, whether the characteristics of the GRF/LR would change with the development of fatigue still needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies on the effects of fatigue during landing activities have demonstrated different responses in ground reaction force (GRF) characteristics [16–19]. Smith et al and Kellis and Kouveliod found a decrease in peak GRF under fatigued conditions during DL [16, 17], but no differences were observed in peak GRF between nonfatigued and fatigued conditions during the same landing task [18, 19]. The causes of these different responses are multifactorial.…”
Section: Introductionmentioning
confidence: 99%